Incidencia del confinamiento de los residuos orgánicos de la parroquia Santa Cecilia en la vida útil del relleno sanitario del cantón Lago Agrio - Esparza Intriago, Cristian Alexander (2015)
The present investigation called was developed in two stages of research, first in the parish of Santa Cecilia belongs to Canton Lago Agrio, Sucumbios Province at a height of 327 m with an average temperature of 25 ° C and partly in the county landfill, in the parish Nueva Loja located at an altitude of 305 m and an annual rainfall of 3000 mm. Production per capita waste generation from 0,773 kg / inhabitant was determined for Santa Cecilia. / Day with a percentage of 67,76% of these residues corresponding to the organic fraction, meaning that at the end of 2014, Santa Cecilia Parish produce a total of 455,54 tons of solid waste. Separate collection system operating in the parish of Santa Cecilia, same which provides two classifications were studied; Blue Case for recyclables (paper, cardboard, plastic, glass and metals) and black / common case for non-recyclable waste (paper and cardboard dirty diapers, sanitary napkins and paper covers, candy, flex and foam packaging waste organic). It was determined that separate collection system shows a low level of recovery of waste, with a percentage of 12,10% while the remaining 87,90% of waste corresponds to the loss. Finally the effect on confinement of these organic waste in the landfill Lago Agrio Canton results in reduced annual space of 1,87% that would be achieved increase the life of the landfill in 11 months of operation and will represent savings of 1.101.934,50 USD to GADMLA. Furthermore, a proposal is presented to strengthen the system of integrated management of solid waste in the parish of Santa Cecilia through the implementation of family composting.